2016
DOI: 10.1155/2016/4858976
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Gestational Diabetes Mellitus Predicting the Needs for Insulin Therapy

Abstract: Objective. To identify factors predicting the need for insulin therapy in pregnancies complicated by gestational diabetes mellitus (GDM). Methods. A total of 1352 patients with GDM diagnosed by the 75-g/2-h oral glucose tolerance test (OGTT) were enrolled in this study. Univariate and multivariate analysis were performed; receiver operating characteristics (ROC) were also drawn. Results. There was a significant difference in factors such as maternal age, pregestational BMI, first visit SBP, first visit DBP, FB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
5
18
1
Order By: Relevance
“…In the first study, logistic regression analysis showed that gestational weeks at GDM diagnosis, plasma glucose levels in a 75‐g OGTT at 1 h and HbA1c were significant predictors for insulin therapy. Similar to the present results , other studies showed that plasma glucose levels in a 75‐g OGTT at 1 h and HbA1c were associated with the need for insulin therapy. In particular, Watanabe et al .…”
Section: Discussionsupporting
confidence: 91%
“…In the first study, logistic regression analysis showed that gestational weeks at GDM diagnosis, plasma glucose levels in a 75‐g OGTT at 1 h and HbA1c were significant predictors for insulin therapy. Similar to the present results , other studies showed that plasma glucose levels in a 75‐g OGTT at 1 h and HbA1c were associated with the need for insulin therapy. In particular, Watanabe et al .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, elevated fasting glucose level at the time of OGTT had been a strong factor associated with insulin therapy in pregnancy. Different cut-off values based on applied criteria for diagnosis of GDM were reported for this association [4547]. Another report by Langer showed that fasting glucose > 105 mg/dL was associated with fetal macrosomia, hypoglycemia in newborn infants, cesarean delivery, and a need for insulin therapy [48].…”
Section: Discussionmentioning
confidence: 99%
“…[2] However, the proportion may be higher among women with GDM because of the effects of nutritional therapy and exercise, which are the main methods used to control blood glucose in GDM. [8] The prevalence of GDM in China has recently increased to 14.7–20.9%, [9] which represents epidemic proportions. Therefore, it is essential to understand whether abnormal GWG is associated with pregnancy outcomes in women with GDM.…”
Section: Introductionmentioning
confidence: 99%